Medium-term results of application of a new method of osteosynthesis in a patient with comparated fracture of the patella (clinical example) - Yu. D. Kim; D. S. Shitikov; N. E. Likholatov; A. V. Shmelkov; O. D. Bagdulina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
In the structure of injuries among patients with fractures of the patella, patients of working age prevail, placing high demands on the functional results of surgical treatment and terms of recovery. Given the low incidence of this pathology in the structure of all injuries of the musculoskeletal system, the authors are of the opinion that patients with patella fractures should receive specialized care that meets the requirements for certain types of fractures in trauma hospitals of any level. The described clinical example describes the medium-term results of treating a patient using a patented method of osteosynthesis of the patella that meets both the requirements of patients and the basic principles of osteosynthesis of intra-articular fractures. The data provided is characterized as good, the use of the patented method is regarded as expedient.